Analisis Kualitas Layanan Terhadap Kepuasan Pelanggan Di Bank Mega Trans Studio Mall Bandung Dengan Kinerja Karyawan Sebagai Variabel Intervening - Putri, Ghaisani Khairana; Indriya, Abdurrahman Faris (eProceedings of Management, 2024)
This research aims to study how service quality affects customer satisfaction at Bank Mega Trans Studio MallBandung Branch, with employee performance to be labeled as the intervening variable. This research also aims toprovide suggestions to Bank Mega Trans Studio Mall Bandung Branch on how to improve their service andcustomer satisfaction. In this research, case study method was used to investigate the relevant phenomenon. Datacollection was conducted through a survey using questionnaires distributed to 367 Bank Mega customers at TransStudio Mall Bandung Branch. The data was then analyzed by applying classical assumption test and path analysis.This research has a positive impact on the advancement of management science, especially in the field of marketingand customer service. In addition, the results of this research can provide valuable input for Bank Mega TransStudio Mall Bandung Branch in an effort to improve their customer service and satisfaction. From the results of thestudy, it was concluded that service quality and employee performance have a positive and significant impact oncustomer satisfaction. In addition, it was found that employee performance acts as a mediator in the relationshipbetween service quality and customer satisfaction. Keywords-customer satisfaction, employee performance, service quality